Pengaruh Store Atmosphere Terhadap Kepuasan Pengunjung Di FudgyBro Blok M: Studi Kuantitatif tentang Pengalaman Kuliner Perkotaan dan Perilaku Konsumen - Dina fatmala; Sukirman, Oman; Pratama PUtra, Gilang (Universitas Muhammadiyah Pontianak, 2026)
This study aims to analyze the influence of store atmosphere on visitor satisfaction at Fudgybro Blok M. A quantitative approach using a survey method was applied, involving 399 respondents selected through purposive sampling. Data were collected through Likert-scale questionnaires and analyzed using simple linear regression. The findings reveal that store atmosphere has a positive and significant effect on visitor satisfaction, with a regression coefficient of 0.550 and an R² value of 0.962. These results indicate that store atmosphere is a dominant factor influencing satisfaction. The study highlights the importance of optimizing atmospheric elements to enhance visitor experience and customer loyalty. Keywords: Store Atmosphere; Visitor Satisfaction; Culinary Tourism; Consumer Behavior; Servicescape; Urban Tourism; Customer Experience; F&B Industry